(untitled) (Research, Society and Development, 2022)
To present a clinical case report of successful endodontic retreatment, in a maxillary first molar, with symptomatic apical periodontitis in the mesiobuccal root that had already undergone endodontic treatment and paraendodontic surgery. A patient was referred for evaluation of upper right first molar with swelling, severe pain and sensitivity to percussion and palpation. She reported having undergone endodontic treatment 1 year ago and, 6 months later, when the symptoms returned, a paraendodontic surgery was performed by the same professional. A cone-beam computed tomography (CBCT) was requested and the images showed extensive bone rarefaction associated with the mesiobuccal root, which had the MB1 canal treated and the MB2 canal untreated. The periapical region of the apices of the distobuccal and palatine roots showed signs of normality, and the treatment plan was established with selective endodontic retreatment only in the mesiobuccal root, with the location and treatment of the MB2 canal and retreatment of the MB1 canal. Retreatment was performed in 2 sessions with an intracanal dressing with calcium hydroxide paste. The canals were filled with Biodentine (BD, Septodont, Saint Maur de Fossés, France). Clinically, the patient had no further signs or symptoms and tomographic images showed evidence of bone repair after 24 months. Correct planning and execution of all phases of endodontic retreatment were fundamental for the success of this case report.